2017
DOI: 10.1371/journal.pone.0181953
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of early warning properties in the Kuramoto model and in an atrial fibrillation model due to an external perturbation of the system

Abstract: When a complex dynamical system is externally disturbed, the statistical moments of signals associated to it can be affected in ways that depend on the nature and amplitude of the perturbation. In systems that exhibit phase transitions, the statistical moments can be used as Early Warnings (EW) of the transition. A natural question is thus to wonder what effect external disturbances have on the EWs of system. In this work we study the impact of external noise added to the system on the EWs, with particular foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Hwang et al (2016) and Hwang et al (2017) examined the effect of the ANS on arrhythmogenesis where the role of ganglia on the initiation of AF is highlighted. The concept of early warning that can forecast a change of system’s stability is applied in AF electrophysiology (Garcia-Gudino et al, 2017). In this study, a cellular automaton is used to describe atrial conduction on the tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Hwang et al (2016) and Hwang et al (2017) examined the effect of the ANS on arrhythmogenesis where the role of ganglia on the initiation of AF is highlighted. The concept of early warning that can forecast a change of system’s stability is applied in AF electrophysiology (Garcia-Gudino et al, 2017). In this study, a cellular automaton is used to describe atrial conduction on the tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Using TS analysis [7, 15], it was found that the Ising model has a critical temperature value T C ≈ 2.27, while the critical coupling constant in the Kuramoto model is close to K C ≈ 1.65, however, the effects of finiteness and periodicity of the mesh, as well as the effect of finite oscillators, can cause the critical value to be slightly displaced. It was also shown that both models have a change in its behavior as the control parameter approaches to the critical value (from above and below).…”
Section: Resultsmentioning
confidence: 99%
“…As future work there are some other systems, as the atrial model presented in [15], in which it will be desirable to check this visualization algorithms. Also, it will be interesting to probe if other algorithms for building networks, as the one proposed in [30], would preserve this characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations